The Effects of Entity Shielding on Claims to Assets: Implications for Financial Reporting (Global Journal of Management and Business Research, 2022)
Strong entity shielding enables corporations to shield firm assets not only from shareholders but also from each shareholder#x2019;s personal creditors. This implies that corporations, not shareholders, own the firm assets. This paper tests this implication by examining legal scholarship on shareholder ownership. The results indicate that, unlike sole proprietors, shareholders have no legal claims to firm assets. This result responds to FASB/ISAB convergence discussions regarding whether corporate reports should take a proprietary or entity perspective. Shareholders have no claims to firm assets, yet balance sheets imply shareholders have exclusive claims to net assets, identical to those of sole proprietors. Therefore, the propriety perspective appears inappropriate for corporate balance sheets. The paper discusses how standard setters can use entity shielding to determine claims to firm assets as a principled approach to differentiate reporting perspectives among reporting entities.
Keywords: reporting entity; reporting perspective; entity shielding; liquidation protection